Comparative performance of submerged and non-submerged pico-Scale crossflow water turbine - Alifarsya Ihsan Maulana; Warjito; Budiarso (BKS-TM Indonesia, 2025)
Indonesia’s abundant renewable energy potential. has driven the nation to shift toward clean energy, including small-scale hydropower systems like picohydro. With capacities under 5 kW, picohydro systems are ideal for remote areas due to their simplicity and low operational costs. Crossflow turbines are commonly used for their efficiency under low-head and fluctuating-flow conditions. This study compares turbine performance under three submergence conditions: unsubmerged, partially submerged, and fully submerged. Two methods were employed: analytical calculations (based on velocity triangles to determine speed, torque, and efficiency) and numerical simulations using CFD software ANSYS Fluent. The turbine geometry was modeled in Autodesk Inventor, with a focus on key performance parameters such as torque, power output, and efficiency. Results show that submergence level significantly affects turbine performance. The unsubmerged condition yielded the highest efficiency and power output, as the nozzle flow enters without downstream fluid resistance, allowing optimal energy transfer to the blades. In contrast, partial and full submergence introduced backpressure zones, air pockets, and vortices that increased drag and reduced net torque. Although absolute torque tended to rise due to greater fluid interaction, the RPM decreased, and energy losses increased, resulting in reduced overall power and efficiency.